The Impact of Accounting Information Systems on Organization Performance in Malaysian Small and Medium Sized Enterprises - Mousa Sabti, Yousif; Ali Alqudhaye, Nael Jaafar; Jaber Al Mousawi, Kawthar Mowaffak; Taengkliang, Buppachat (South Asian Journal of Social Sciences and Humanities, 2023)
This study aims to attain a set of goals that is the most significant of which are: identifying the  factors causing the success of accounting information systems (AIS) and their repercussions  on the performance of organizations in Malaysian small and medium sized enterprises. This  paper utilised 101 small and medium enterprises from 2015 to 2020. The results show there are  a positive effect of AIS on organizations performance. The AIS supporting the performance and raise the quality of the organization’s performance. The study recommended the need to  give special priority to attention to the quality of the AIS and the importance of developing  AIS continuously in line with the needs and desires of the beneficiaries.
Keywords: Malaysia; accounting information systems; organization performance